(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article scientifically studies ways to increase the efficiency of beekeeping systems based on intensive technologies in the ecological and climatic conditions of the Fergana region. The study assessed the flowering period of plants, microclimatic factors, colony strength, disease prevalence, and the effectiveness of modern technological solutions. The results show that the introduction of intensive technologies adapted to local conditions significantly improves honey yield, colony stability, and economic indicators of the farm.